Caplacizumab reduces the frequency of major thromboembolic events, exacerbations and death in patients with acquired thrombotic thrombocytopenic purpura. (5th June 2017) - Peyvandi, F.; Scully, M.; Kremer Hovinga, J. A.; Knöbl, P.; Cataland, S.; De Beuf, K.; Callewaert, F.; De Winter, H.; Zeldin, R. K.
Abstract : Essentials Acquired thrombotic thrombocytopenic purpura (aTTP) is linked with significant morbidity/mortality. Caplacizumab's effect on major thromboembolic (TE) events, exacerbations and death was studied. Fewer caplacizumab‐treated patients had a major TE event, an exacerbation, or died versus placebo. Caplacizumab has the potential to reduce the acute morbidity and mortality associated with aTTP. Summary: Background: Acquired thrombotic thrombocytopenic purpura (aTTP) is a life‐threatening autoimmune thrombotic microangiopathy. In spite of treatment with plasma exchange and immunosuppression, patients remain at risk for thrombotic complications, exacerbations, and death. In the phase II TITAN study, treatment with caplacizumab, an anti‐von Willebrand factor Nanobody ® was shown to reduce the time to confirmed platelet count normalization and exacerbations during treatment. Objective: The clinical benefit of caplacizumab was further investigated in a post hoc analysis of the incidence of major thromboembolic events and exacerbations during the study drug treatment period and thrombotic thrombocytopenic purpura‐related death during the study. Methods: The Standardized Medical Dictionary for Regulatory Activities (MedDRA) Query (SMQ) for 'embolic and thrombotic events' was run to investigate the occurrence of major thromboembolic events and exacerbations in the safety population of the TITAN study, which consisted of 72 patients, of whom 35 received caplacizumab and 37 received placebo. Results: Four events (one pulmonary embolism and three aTTP exacerbations) were reported in four patients in the caplacizumab group, and 20 such events were reported in 14 patients in the placebo group (two acute myocardial infarctions, one ischemic stroke, one hemorrhagic stroke, one pulmonary embolism, one deep vein thrombosis, one venous thrombosis, and 13 aTTP exacerbations). Two of the placebo‐treated patients died from aTTP during the study. Conclusion: In total, 11.4% of caplacizumab‐treated patients and 43.2% of placebo‐treated patients experienced one or more major thromboembolic events, experienced an exacerbation, or died. This analysis shows the potential for caplacizumab to reduce the risk of major thromboembolic morbidities and mortality associated with aTTP.